عالمية الدعوة القرآنية للسلام وسبل تقريبها: قراءة في التفسير المنهاجي للإمام عبد السلام ياسين: The Global Quranic Call for Peace & Its Implementation: Reading in Al-Tafsir Al-Minhaji of Imam Abdessalam Yassine - Abdulrahman Obeid Hussein; Adnan Mohd Abdullah Shalash (Maʿālim al-Qurʾān wa al-Sunnah, 2021)
The problem statement of this research is about Imam Yassine’s thought in his reading of Islamic past and present and Western intellectual trends, and about his long experience in the field of Da’wah, as Imam Yassine urged Muslims to be capable of handling the mission of the holy Quran. It becomes more complicated with Al-Tafsir al-Minhaji as an approach to interpret the holy Quran and ease it for Muslim youth understanding in Imam Yassine’s books about thought, education, Da’wah, mysticism and civilization. This research aims to explain how Al-Tafsir al-Minhaji concerns about the method of practicing Quranic interpretation in Da’wah for Muslim Ummah renaissance. The research also aims to highlight that achieving global peace is one of main Quranic objective that Muslim thinkers are paying a great attention to its role in dialogue between variant sectarianists and theologians. Researchers followed the descriptive and inductive methods to explore Yassine’s views about peace, civilization and argumentation. Some findings of this research: Imam Yassine confirms the necessity of coincidence between the Quranic objectives and political objectives; and calls for dialogue based on Quranic objectives and its component of wisdom and dynamic argumentation, which leads to peace. To understand the fluctuation of history in the light of Quranic exegesis, Imam Yassine scrutinized the Quranic objectives of peaceful coexistence and cultural exchange.